Hydraulic Analysis of the Samarra-Al Tharthar System - Mohammed Sadeq Abdulwahid Abdulridha; Hayder A. Al Thamiry, Ass. Prof. Dr. (Journal of Engineering, 2017)
Low incoming discharge upstream of Samarra-Al Tharthar System leads to sediment accumulation and forming islands, especially an island upstream of Al Tharthar Regulator. This island and the sedimentation threaten the stability of the structure and reduce the efficiency of the system. This study aims to hydraulically identify the sedimentation problem mentioned above, to find solutions of how to control the sediment problems, and to develop the capacity of the system for 500 years return period flood of 15060 m3/s. Surface Water Modeling System (SMS10.1) with two dimensional depth average models (RMA-2) software were used to simulate and analyze the system. The results of analysis showed that the maximum permissible discharge through the system was 8250 m 3/s where the discharge from Samarra Barrage was 2400 m3/s to avoid flooding in Baghdad city. The water surface level could be lowered during constructing; the new Al Tharthar Regulator expansion capacity of 7000 m3/s in the case of peak flood (15060 m3/s) to 68.51 m.a.m.s.l. upstream of Samarra Barrage by dredging the island and channel. On the other hand, during constructing the guide bank, and dredging the island and channel, the water surface elevation was 68.91 m.a.m.s.l. upstream of Samarra Barrage.